Artful Instruction: Refining TVET Pedagogy on Food Safety Requirements - Arihasnida Ariffin,; Suhaizal Hashim,; Khairul Anuar Abdul Rahman,; Xu Wenjun, (Online Journal for TVET Practitioners, 2024)
Food safety is a critical issue in the culinary industry, and culinary students as a Technical and Vocational Education and Training (TVET) practitioners must understand the importance of adhering to food safety requirements. However, there are several challenges in ensuring students' perceptions of conformity to food safety requirements are accurate and effective. These issues include the complexity of food safety regulations, the varying levels of understanding among students, and the limited resources available to culinary programs to provide comprehensive training. This study explores vocational culinary students' perceptions of conformity to food safety requirements. The research employs quantitative design research, using surveys to collect data from 120 students enrolled in culinary programs at vocational schools in Johor, Malaysia. The study aims to understand how students view their adherence to food safety protocols and how their training and education shape their perceptions. This study is structured as a survey employing a distribution of questionnaires to find culinary students in Johor, Malaysia views compliance with food safety requirements in terms of food safety training, food safety rules, food safety standards, and license compliance with food safety standards. Statistical Package for Social Science (SPSS) version 26.0 was used to compute the survey responses' mean value, standard deviation, and frequency. All of the responses to the research questions got a high mean score, as the mean score value for food safety training (M=4.39), food safety rules (M=4.40), food safety standards (M=4.37), and license compliance with food safety standards (M=4.36). The results reveal that most students understand food safety practices well, but there needs to be more knowledge and implementation of some critical protocols. Furthermore, the study revealed that vocational students' general perceptions of food safety laws regarding food safety rules had the highest mean value, indicating that this is the most influential factor in persuading how culinary students in Johor, Malaysia perceive compliance with food safety standards. These findings have implications for culinary education programs and the food service industry, suggesting that more attention should be paid to providing students with comprehensive training in food safety practices to ensure safe and healthy food preparation.